ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA AUDITOR PADA KANTOR AKUNTAN PUBLIK DI SURAKARTA, SEMARANG DAN YOGYAKARTA - Djoko Kristantianto, Anissa Kezia Damayanti, Rispantyo & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2018)
This research aims to analyze the factors that affect the performance of auditors. This research is a survey research at Public Accounting Firms in Surakarta, Semarang and Yogyakarta. The study took primary data by spreading the questionnaire. Sampling technique in this research use purposive sampling. The number of respondents of this study is 55 respondents, but the return and can be processed is 48 questionnaires. Technical analysis used is’multiple’linear regression’analysis. The result of this research shows that: (1) Locus Of Control has positive and not significant effect on auditor performance, (2) Auditor Professionalism has positive and significant influence to auditor performance, (3) The leadership style take effect positive and significant to the auditor's performance, (4) Organizational Commitment take effect negative and not significant on auditor's performance, (5) Professional Ethics take effect negative and not significant on auditor performance.Keywords: Locus of control, Auditor professionalism, Leadership style, Organizational commitment, Professional ethics, Auditor performance